Risiko kanker payudara pada penderita gondok endemik di lereng merapi jawa tengah - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1991)
ABSTRAk The risk of breast cancer in endemic goiter women patients can be estimated from the serum copper/zinc ratio. The contents of copper and zinc in sera of female goiter patients, of the endemic Sawangan Sub-district, and of female normal patients, of the non endemic Mungkid Sub-district, near the Merapi volcano, were measured by atomic absorption spectrometry. Based on the goiter class and age, the mean concentration of copper and zinc of goiter patients were higher than that of normals, but the mean copper/zinc ratio was lower in goiter patients than in normals. This is an indication that the goiter endemic female patients were not as risk of breast cancer.